WASTES GENERATED, WASTES MANAGEMENT IN KANO ABATTOIR, DALA LOCAL GOVERNMENT AREA, KANO STATE, NIGERIA - Ogamba, Confidence Chidera; Bukar, A. Abdullahi (FUDMA Journal of Sciences, 2023)
High production of meat for human use has resulted to extreme waste generation from abattoirs. Nigeria as a developing nation has been characterized by incompetent waste disposal, treatment, and management technologies leading to pollution.  This study was conducted to assess wastes generation and management in Kano Abattoir. An investigative survey approach was used to assess the Wastes generated and management in Kano Abattoir, Kano State. This was investigated using personal communication and interview with the staff, workers and meat sellers of the Abattoir. Waste generated was estimated based on Aniebo calculation. The assessment was carried out for six months during dry and wet season (February – April for dry season and June – August for wet season).  The sum total of 131,737 cows and goats were slaughtered for both seasons (dry and wet season) in Kano Abattoir. For female and male cows about 766.6 ton of blood, 486.8 ton of intestinal contents, 389.5 ton of waste tissue and 718.1 ton of waste bone, total of 2,361.3 tons of wastes were discharged for dry and wet seasons in Kano Abattoir while for female and male goats, 51 ton of blood, 88.5 ton of intestinal contents, 56.6 ton of waste tissue and 145.9 ton of waste bone, total of 342.1 tons of wastes were discharged for the dry and wet seasons in Kano Abattoir. The Abattoir visited used nearby stream as means of discharging these effluent there by giving offensive odour to the environment, contributing to the organic and nutrients of the...
Keywords: Abattoir; Wastes generated; Wastes management; Pollution; Environment